Llama Llama Misses Mama - Dewdney, Anna (New York : Viking, 2009)
Llama Llama experiences separation anxiety on his first day of nursery school.
Keywords: Stories in rhyme; Separation anxiety -- Fiction; Nursery schools -- Fiction; Schools -- Fiction; Llamas -- Fiction